EFFECT OF MATING DURATION ON FECUNDITY (REPRODUCTIVE PARAMETER) OF ERI SILK MOTH PHILOSAMIA RICINI IN DIFFERENT SEASONS - Batham, Rajkumari; Yadav, Ulka (International Journal of Research -GRANTHAALAYAH, 2015)
Production of viable eggs in the Eri silkworm, Philosamiaricini is influenced by the mating activity.The effect of coupling duration on the fecundity of Eri silkworm, Philosamiaricini during different seasons was studied. Fecundity rate inEri silkworm, PhilosamiaRicinidoes notsignificant variation with increase in mating duration were observed different season.